Age related morphological alterations in elderly women - Elisa Ribeiro dos Santos; Tatiane Hallage; Cosme Buzzachera; Maressa Krause; Sergio da Silva (Universidade Federal de Santa Catarina, 2006)
The purpose of the present study was to present the morphological profile of elderly women from differentage groups. The sample was made of 1,016 women, with age greater than 60 years. The following anthropometricvariables were measured: body mass, height, circumferences and skin folds and percent body fat was calculated.The mean values of the variables body mass, height, body mass index, circumferences and skin folds decreasedin the younger women group when they were compared to the oldest women. More expressive declines occurredin arm, midthigh, and medial calf circumferences, indicating a possible smaller muscle mass in older populations.Despite the fact that the body mass index mean values classify elderly women, predominantly, as overweight, itseems that the individuals that reach older age are those that present less body fatness. It´s suggested that futurestudies investigate these modifications in different populations, as elderly men. RESUMO O objetivo do presente estudo foi apresentar o perfil morfológico em diferentes faixas etárias de mulheresidosas. A amostra foi constituída de 1016 indivíduos do sexo feminino, com idade superior a 60 anos. Forammensuradas as seguintes variáveis antropométricas: massa corporal, estatura e circunferências, dobras cutânease posterior cálculo do percentual de gordura. Os valores médios das variáveis: massa corporal, estatura, índice demassa corporal, circunferências e dobras cutâneas das mulheres mais jovens reduziram, quando comparadas àsmais idosas. Os declínios mais expressivos ocorreram nas circunferências de braço, coxa média e panturrilhamedial, indicando, possivelmente, uma menor massa muscular em populações mais idosas. Apesar dos valoresmédios do índice de massa corporal classificar em as mulheres idosas, predominantemente, com sobrepeso,parece que os indivíduos que alcançam as idades mais avançadas são aqueles que apresentam menor adiposidadecorporal. Sugere-se que futuros estudos busquem investigar essas modificações em diferentes populações,como os idosos do sexo masculino.